Indonesian tourism between international volatility and domestic stability - Hidayati, Inayah (Priviet Social Sciences Journal, 2026)
This study investigates the dynamics of Indonesian tourism from 2000 to 2024, emphasizing the dual roles of international tourist arrivals and domestic tourist trips. The analysis examines how international markets exhibit volatility in response to global crises, whereas domestic tourism demonstrates notable stability and resilience. This research employs official secondary data from Statistics Indonesia, including annual international arrivals, monthly arrivals by nationality, domestic trips by province of origin and destination, and tourism foreign exchange earnings. All datasets were standardized into a panel format and analyzed using descriptive quantitative methods combined with the periodization of crisis and recovery phases. The findings show that international arrivals are highly volatile, with sharp declines during the 2003 SARS episode, the 2008 global financial crisis, and especially the COVID-19 pandemic, with an approximately 80% drop in 2020–2021. In contrast, domestic trips reached 2.9 billion in 2019 and recovered quickly, surpassing 3.3 billion in 2023. Foreign exchange earnings move in tandem with international arrivals, averaging more than US$10 billion annually before 2014 and falling during crisis episodes. This evidence underscores a structural duality: international arrivals remain crucial for foreign exchange and global positioning, whereas domestic trips provide the backbone of resilience and local economic continuity. Policy implications include diversifying international markets, enhancing domestic tourism infrastructure and connectivity, and embedding the principles of resilient and sustainable tourism in national strategies.